The Importance and Value of Older Employees Wise Workers in the Workplace - Hilsen, Anne Inga (Springer Nature, 2021)
This open access book makes a contribution to our understanding of one of the social challenges facing many western nations i.e. the challenge of an ageing population. It specifically addresses the issue of competence among older employees. Others have studied ageing populations in terms of the economic burden or the pressure on healthcare services and generally view the rising numbers of seniors more as a challenge than an opportunity. In this book, authors discuss ways of gaining positive benefits from our ageing and more experienced work force.